Equivalence trial of azithromycin to benzathine penicilling in the treatment of syphilis - Passos, Mauro R.L.; Benzaken, Adele S.; Coêlho, Ivo C.B.; Rodrigues, Gerson H.S.; Dutra Junior, João Catarino; Varella, Renata Q.; Tavares, Rogério R.; Barreto, Nero A.; Marques, Bruno P.; Figueiredo, Jair (Brazilian Journal of Sexually Transmitted Diseases, 2004)
Introduction:although syphilis is a milenar disease and, notwithstanding the existence of STD/AIDS programmes in many countries, this diseasecontinues to be a public health problem throughout the world. Objectives:to determine azithromycin equivalence (non-inferiority) to benzathinepenicillin in the treatment of acquired syphilis in the recent (primary and secondary) and early latent phase (up to one year ́s duration). Methods:experimental, randomized, multicentric equivalence (non-inferiority) trial. Research subjects were divided in four groups: Group 1 – treated with2.400.000 U IM of benzathine penicillin in a single dose (one 1.200.000 U IM dose applied to each gluteal or deltoid muscle); Group 2 – treated withtwo benzathine penicillin 2.400.000 U IM doses (one 1.200.000 U applied to each gluteal or deltoid muscle), one week apart, total dose of 4.800.000U ; Group 3 – treated with azithromycin 1g PO – two doses one week apart – total dose of 2g and Group 4 – treated with azithromycin 1g PO weeklyfor 3 weeks – total dose of 3g. Diagnostic methods: bacterioscopy of cutaneous-mucosal lesion smear if present (dark-field or immunofluorescence)and serological tests (VDRL – Biolab/Merieux and FTA-Abs for confirmation – Biolab/Merieux). Cure criteria were, in patients with lesions, thedisappearance of the lesions, and as serological criteria the four-fold decrease in VDRL titers or its negativation in a period of six months. Samplesize for equivalence test was determined to be valid by the use of statistical software (StudySize 1.0, Creostat HB, Sweden) postulating a 10% maxi-mum of inferiority in efficacy of azithromycin when compared to benzathine penicillin in the evaluated treatment schemes with p = 0.05 in a random,paired, equal size groups trial. Confidence interval analysis was done to interpret results, according to ICH document E-10. Results:200 patientsentered the study. 33 (16.18%) abandoned it. Of the 171 patients which underwent the complete protocol, 71 (41.52%) were female and 100(58.48%) were male. 35 of 171 (20.47%) had early latent syphilis; 136 of 171 (79.53%) had recent syphilis (primary and secondary). 11 patients(6.43%) presented a Jarish-Herxheimer reaction. Of the patients that agreed to submit to HIV testing 9 were positive. The cure rates were: Group 1 –39/44 (88.64%); Group 2 – 38/42 (90.48%); Goup 3 – 37/40 (92.5%); Group 4 – 43/45 (95.55%). None of the subjects interrupted the treatmentbecause of side effects or hypersensitivity to the medications. Analysis of data showed C-T<M (refusal of inferiority hypothesis) by a wide marginwhen comparing Group 1 to Group 3 (one penicillin dose x lower dose azithromycin) and Group 2 to Group 4 (two penicillin doses x higher doseazythromycin) results. Conclusion:Azithromycin was shown to be equivalent to benzathine penicillin in the evaluated treatment schemes. Both weresafe and effective for the treatment of recent or early latent syphilis. The drugs were well tolerated in the utilized doses. No important side effectsapart from Jarisch-Herxheimer reaction were seen.